A validated method to measure benzo[a]pyrene concentrations in tobacco by high-performance liquid chromatography-fluorescence detection. Issue 4 (19th January 2015) - Carradus, M.; McAdam, K. G.; van Heemst, J. D. H.; Goss, C. H. A.; Wright, C.
Abstract : This publication describes a validated method suitable for the quantification of benzo[ a ]pyrene (B[ a ]P) in tobacco blend and smokeless tobacco products by High-Performance Liquid Chromatography-Fluorescence Detection (HPLC-FLD). Abstract : This publication describes a validated method suitable for the quantification of Benzo[ a ]Pyrene (B[ a ]P) in tobacco blend and smokeless tobacco products by High-Performance Liquid Chromatography-Fluorescence Detection (HPLC-FLD). Samples were hydrated and extracted with a mixture of hexane and acetone. For the quantification of levels of B[ a ]P the sample extracts were subjected to adsorption chromatography using base-modified silica to remove co-extracted substances. The concentrated final extract was re-dissolved in acetonitrile and analysed by HPLC with fluorescence detection (FLD). B[ a ]P and the internal standard, deuterated B[ a ]P (D12 -B[ a ]P) were resolved chromatographically. The method was validated and determined to be fit for purpose for the quantification of B[ a ]P in tobacco from 3R4F Kentucky reference cigarettes, a flue-cured Virginia cigarette tobacco blend containing 10% air-cured Burley tobacco, and a Tanzanian dark fire-cured cigarette blend. The method was also validated for smokeless tobacco products including commercially available dry snuff, soft pellet tobacco and pouched snus products over the concentration range of 0.38 ng g −1 to 150 ng g −1, based on extraction of a 0.5–2 g aliquot of sample. The measurement uncertainty at a confidence interval of approximately 95% was estimated from data generated by three analysts using two instruments on three separate occasions using matrix (pouched snus) fortification experiments. The expanded uncertainty of the method was ±21.3% of the mean B[ a ]P concentration.